Learning approaches as predictors of academic performance of undergraduate students in Ahmadu Bello Universiy, Zaria - Ladan, Muhammad Awwal; Balarabe, Fatima; Sani, D.K.; Musa, H.A.; Salihu, A.A.; Salihu, M.A. (International Organization Of Scientific Research, 2014)
Background: The research was conducted to investigate learning approaches as predictors of academic performance of undergraduate students in Ahmad Bello University, Zaria. The aim was to assess the learning approach of undergraduate students in Ahmadu Bello University, Zaria. The objectives are to determine the predominant learning approach, identify factors that influence the students learning approach and explore the relationship between approaches to studying and academic achievement of undergraduate students of Ahmadu Bello University, Zaria. Materials and methods: A non-experimental descriptive survey method was employed and analysis was done using SPSS version 21. The sample technique was probability (simple random) type of sample technique base on faculty. The sample size was calculated to 395 using Yamane formula. 395 questionnaires were administered out of which 375 were retrieved. Results: The study shows that 81.1% of the students were aware of learning approach and the predominant learning approach mostly used by Ahmadu Bello University, Zaria undergraduate students is surface approach (M=14.88,SD=2.64). The study identified personal factors, family factors, school factors and peer factors and social factor as factors that influence the students learning approach. It also shows that there is a significant relationship between learning approach and academic achievement (R=0.205,p=0.005).